Can financial incentives reduce the baby gap? Evidence from a reform in maternity leave benefits - Anna Raute (Queen Mary University of London, School of Economics and Finance, 2018)
In this paper, I assess whether earnings-dependent maternity leave positively impacts fertility and narrows the baby gap between highly educated (high-earning) and less-educated (low-earning) women. I exploit a major maternity leave benefit reform in Germany that considerably increased the financial incentives, by up to 21,000 EUR, for highly educated and higher-earning women. Using the large differential changes in maternity leave benefits across education and income groups in a differences-in-differences design, I estimate the causal impact of the reform on fertility for up to 5 years. In addition to demonstrating an up to 23% increase in the fertility of tertiary-educated women, I find a positive, statistically significant effect of increased benefits on fertility, driven mainly by women at the middle and upper end of the earnings distribution. Overall, the results suggest that earnings-dependent maternity leave benefits, which compensate women according to their opportunity cost of childbearing, could successfully reduce the fertility rate disparity related to mothers' education and earnings.
Keywords: J13; J16; J18; 330; Fertility; fertility gaps; paid maternity leave; opportunity cost; Elternzeit; Wirkungsanalyse; Fertilität; Weibliche Arbeitskräfte; Hochqualifizierte Arbeitskräfte; Schätzung; Deutschland